The clinical impact of plasma goblet cell and exocrine pancreas antibodies in discriminating Crohn’s disease and ulcerative colitis - Erzin, Yusuf; Çelik, Aykut F.; Karatoka, Belma; Aslan, Mustafa; Kocazeybek, Bekir (Cerrahpaşa Medical Journal, 2014)
Objectives: Despite the increasing incidence of inflammatory bowel diseases (IBD) it may be challenging sometimes to discriminate Crohn’s disease (CD) and ulcerative colitis (UC). Although antibodies to exocrine pancreas (PAB) and Goblet cells (GAB) have been reported to have a low sensitivity and specificity for IBD no study has been performed yet in our country. Our aim was to determine the clinical importance of PAB and GAB in discriminating CD and UC. Methods: Sera of age- sex matched 130 healthy controls (HC), 102 UC, 63 CD patients followed-up at Istanbul University, Cerrahpafla Medical Faculty weekly IBD outpatient clinic were analysed. PAB and GAB were detected by indirect immunofluorescence assay (IFA). Results: The prevalence of GAB was 22/130 (17%), 27/102 (27%), 8/63 (13%) and the prevalence of PAB was 1/130 (0.8%), 2/102 (2%), 8/63 (13%) in HC, UC, CD patients, respectively. When all groups were compared to each other the prevalence of PAB was significantly higher in CD patients compared to HC (χ2=13.503; p= 0.000), and UC patients (p= 0.007), whereas the prevalence of GAB was significantly higher among UC patients compared to CD patients (χ2=4.420; p= 0.036). No significant difference regarding GAB was observed between UC patients and HC. The prevalence of GAB(+)/PAB(-) profile was 22/130 (17%), 26/102 (25%), 6/63 (10%) in HC, UC, CD patients, respectively. When CD patients were compared to UC patients the sensitivity, and specificity of this profile as a marker of CD was 0.25, and 0.84, respectively. The prevalence of GAB(-)/PAB(+) profile was 1/130 (0.7%), 1/102(1%), 6/63 (10%) in HC, UC, CD patients, respectively. When UC patients were compared to CD patients the sensitivity, and specificity of this profile as a marker of UC was 0.10, and 0.99, respectively. No significant correlations were observed between PAB, and GAB and location, clinical activity, the presence of prior resections, acute phase reactants, age, and sex in CD, and UC patients. Conclusion: Although the prevalences of GAB and PAB may vary in different IBD subgroups, the low sensitivity of both markers make them an useless tool in discriminating CD and UC.